The Impact of Ideological Positioning on the Communicative Styles Employed by Governments - García Beaudoux, Virginia; Berrocal-Gonzalo, Salomé; Ana Slimovich; Bruni, Leandro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This paper analyses the relationship between ideological self-positioning and leadership styles communicated on Instagram by twelve female politicians. The research uses content analysis of 1,290 posts made during 2023. The study examines the correlation between the politicians' self-perceived ideological positioning and 1) the type of information communicated (soft information/politainment vs. hard information/political); 2) the projected leadership style (conciliatory/soft vs. firm/hard); 3) the level of personalization in their communications. The results reveal that women government leaders who identify with the right-wing ideological spectrum tend to: employ more politainment strategies; project a more conciliatory leadership style; and use more personalized communication.